Potensi Keefektifan Harapan Ensiklopedia Genus Bulbophyllum Berbasis Potensi Lokal KHDTK Tahura Sultan Adam Mandiangin dalam Melatih Keterampilan Berpikir Kritis Mahasiswa: (Potential Expected Effectiveness of a Bulbophyllum Genus Encyclopedia Based on Local Potential of KHDTK Sultan Adam Mandiangin Tahura in Developing Students’ Critical Thinking Skills) - Khasanah, Khayatun; Zaini , Muhammad (BIODIK, 2026)
Critical thinking skills are a crucial competency to be developed within the context of 21st-century higher education. However, there is still a need to enhance students' critical thinking skills through the use of contextual teaching materials that support the learning process. This study aimed to examine the potential effectiveness of a *Bulbophyllum* genus encyclopedia—based on the local biodiversity of the Sultan Adam Grand Forest Park (Tahura Sultan Adam)—in fostering students' critical thinking skills. The study employed an Educational Design Research (EDR) approach utilizing Tessmer’s formative evaluation model, specifically focusing on the small-group evaluation stage. The participants consisted of four students from the Biology Education Study Program who had previously completed the Phanerogamae course. Data regarding potential effectiveness were gathered through Student Worksheets (LKM)—designed to cultivate critical thinking skills—and an instrument assessing students' metacognitive skills. The data were analyzed using descriptive quantitative methods based on obtained scores to determine the category of potential effectiveness. The results indicated that the *Bulbophyllum* genus encyclopedia achieved a "good" rating across five aspects of critical thinking skills—interpretation, analysis, evaluation, inference, and explanation—as well as in the aspect of self-regulation. These findings suggest that the *Bulbophyllum* genus encyclopedia has the potential to serve as an effective contextual teaching resource—leveraging local biodiversity—for fostering critical thinking skills in university-level biology education. Abstrak : Keterampilan berpikir kritis merupakan salah satu kompetensi penting yang perlu dikembangkan dalam pembelajaran abad ke-21 di perguruan tinggi. Namun, keterampilan berpikir kritis mahasiswa masih perlu ditingkatkan melalui penggunaan bahan ajar kontekstual yang mendukung proses pembelajaran. Penelitian ini bertujuan untuk menguji keefektifan harapan buku ensiklopedia genus Bulbophyllum berbasis potensi lokal Tahura Sultan Adam dalam melatih keterampilan berpikir kritis mahasiswa. Penelitian ini menggunakan pendekatan Educational Design Research (EDR) dengan model evaluasi formatif Tessmer yang difokuskan pada tahap uji kelompok kecil (small group evaluation). Subjek penelitian terdiri atas empat mahasiswa Program Studi Pendidikan Biologi yang telah menempuh mata kuliah Phanerogamae. Data keefektifan harapan diperoleh melalui pengisian Lembar Kerja Mahasiswa (LKM) yang dirancang untuk melatih keterampilan berpikir kritis serta instrumen keterampilan metakognisi mahasiswa. Data dianalisis secara deskriptif kuantitatif berdasarkan skor yang diperoleh untuk menentukan kategori keefektifan harapan. Hasil penelitian menunjukkan bahwa buku ensiklopedia genus Bulbophyllum memperoleh kategori baik pada lima aspek keterampilan berpikir kritis, yaitu interpretasi, analisis, evaluasi, inferensi, dan eksplanasi, serta aspek pengaturan diri. Hasil tersebut menunjukkan bahwa buku ensiklopedia genus Bulbophyllum berpotensi efektif sebagai bahan ajar kontekstual berbasis potensi lokal dalam melatih keterampilan berpikir kritis mahasiswa pada pembelajaran biologi di perguruan tinggi.